Simulation of Acoustic Signals in a Waveguide of Circular Cross Section; Mechanical Engineering, Automation and Control Systems (MEACS) - Shulgina Yu. V. Yulia Viktorovna; Starostin A. L.; Kostina M. A. Maria Alekseevna; Mylnikova T. S. Tatyana Stepanovna; Soldatov A. I. Aleksey Ivanovich (2015, 2015)
Title screen